Avaliação do efeito do Resveratrol na carcinogênese oral induzida por 4-nitroquinolina 1-óxido em camundongos - Freitas, Amanda de Oliveira (2024)
Resveratrol (RSV) is a natural product that has potential in cancer chemoprevention through several molecular targets. The aim of this work was to evaluate the role of RSV in tumor initiation and progression in animal model of oral carcinogenesis induced by 1% 4-nitroquinoline 1-oxide (4NQO). In this sense, 60 Swiss mice were subjected to application of 1% 4NQO on the surface of the tongue five times a week for 20 weeks. The animals were divided into six groups: negative control group (GCN); RSV control group (GCRSV); positive control group (GCP) with 4NQO; and three experimental groups: 4NQO with RSV for 6 weeks (RSV6), 4NQO with RSV for 10 weeks (RSV10) and 4NQO with RSV for 20 weeks (RSV20). RSV was administered at a dose of 8mg/kg/day by gavage. Then, the animals were euthanized after 20 weeks and the tongues were collected for histological analysis. Blood and organ collection was performed for toxicity analysis. For all results, the p<0.05 significance level was considered. Exposure to 4NQO promoted macroscopic changes in the tongue, such as elevations and plaques, and microscopic changes, with the development of microinvasive carcinoma to extensive tissue invasion (p<0.001). Hematological analysis revealed significant leukocytosis in all groups in contact with 4NQO (p<0.001). Regarding systemic toxicity, non-exposure to 4NQO resulted in a significant body mass gain (p<0.001). Microscopic changes were observed in the esophagus, intestine, and liver. When comparing groups, a significant change in the mass of the liver, kidney and spleen was also detected. In conclusion, the present model is capable of developing epithelial changes in the tongue, from severe dysplasias to carcinomas with extensive invasion of adjacent tissues, as well as the esophageal, splenic, hepatic, renal and intestinal levels, potentiating hematological dysregulation and reducing body mass. However, the use of RSV does not interfere with tumor initiation and progression, despite having a protective effect on intestinal villi when used for at least 10 weeks and attenuating the inflammatory infiltrate and the degree of keratinization in the tongue tumor regions when used for 20 weeks.